Impact on the physical activity level of adults at high and very high risk of developing type 2 diabetes mellitus: email follow-up intervention - Carla Giuliano de Sá Pinto Montenegro; Rafael Mathias Pitta; Marcio Marega; Roberta L. Rica; Luis Felipe Tubagi Polito; José Antonio Maluf de Carvalho; Luana Queiroga; Mayra Trevisani; Fabio Ceschini; Danilo Sales Bocalini; Aylton Figueira Junior
Abstract Aims: The present study aimed to assess the effect of a 24-week intervention on the physical activity level among adults at risk of developing type 2 diabetes mellitus (DM2). Methods: It was included 129 individuals of both sexes who underwent the Preventive Health Check-up at the Albert Einstein Israelita Hospital between January and August 2010 and who were at high and very high risk of developing DM2. The risk of developing DM2 was assessed according to the FINDRISC criteria. All participants were evaluated by the International Physical Activity Questioner (IPAQ). Subjects were followed-up for 24 weeks by a physical education professional through emails during a 6 month period. The IPAQ was sent by email after 3 and 6 months of follow-up. Statistical analysis was performed using the chi-square test with p<0.05 and the Yule Coefficient test. Results: At baseline of the follow-up period, 80.3% of individuals failed to comply with the recommended weekly physical activity. In the end, motivational intervention by e-mail encouraged 74.2% of individuals to comply with the weekly-recommended physical activity and only 1.5% were classified as sedentary. Conclusion: Therefore, the follow-up protocol conducted by periodic and personalized e-mails proved to be effective in promoting physical activity among people at risk of developing metabolic diseases.